Generic Determinacy and Money Non-Neutrality of International Monetary Equilibria - Tsomocos, D (2008)
I address the issue of the ‘number’ of international monetary equilibria that the international finance model of Geanakoplos and Tsomocos (2002) possesses. The mainstream competitive model has locally unique equilibria with respect to the real side of the economy; however, it manifests nominal indeterminacy. Kareken and Wallace [Kareken, J., Wallace, N., 1981. On the Indeterminacy of Equilibrium Exchange Rates. Q. J. Econ. 96, 207–222] extend the O.L.G. indeterminacy result to a monetary model of the international economy. However, the role of monetary sector together with the market and agent heterogeneity remove real and nominal indeterminacy in the Geanakoplos and Tsomocos model. In particular, nominal indeterminacy abruptly disappears when private liquid wealth is non-zero. Finally, monetary policy becomes non-neutral since monetary changes affect nominal variables which in turn determine different real allocations. Lucas did not find these non-neutral effects in his model of international finance because he postulated a ‘sell-all model’ in which every agent sells everything he owns in every period. Thus, the number of transactions remain unaffected by definition regardless of any policy changes. Instead, when transactions emerge endogenously in equilibrium monetary policy has non-neutral effects provided that there exist potential gains to trade at the initial allocation of goods.